Apios calcicola (Fabaceae: Papilionoideae: Phaseoleae), a new species from limestone mountains of Southwestern China - Lu, Zhao-Cen; Wei, Lang; Song, Zhu-Qiu; Wei, Su-Juan; Pan, Bo (Phytotaxa, 2025)
Apios calcicola Z.C.Lu & B.Pan bis, from karst terrain of Guangxi and Guizhou Provinces, China, is described here as a new species. This new species resembles two other widespread species, A. carnea and A. fortunei. However, it can be easily distinguished from A. carnea by its twisted and asymmetric flowers and conspicuous tubers, and from A. fortunei by its trifoliolate leaves, and purplish red and larger flowers. Molecular evidence suggests its position related to A. fortunei. Conservation status of A. calcicola is evaluated as Data Deficient (DD). The key to the Apios species is also updated.